Quantitative real-time PCR analysis of gut microbiota in rheumatoid arthritis patients compared to healthy controls - Azin Masroor; Abolfazl Gholipour; Milad Shahini Shams Abadi; Mohammad Mousavi; Moluk Hadi Alijanvand; Behnam Zamanzad (AMB Express)
Abstract Rheumatoid arthritis (RA) is an autoimmune disorder with synovial inflammation of joints and extra articular manifestations. The results of recent researches consider the relationship between microbiota and the immune system as a double-edged sword. Considering that the relationship between the composition of intestinal microbiota and the immunological and clinical status of the body has been confirmed, it is very important to investigate the effect of each genus and species of bacteria on the state of the immune system. The current study was determined using 16S rRNA gene sequencing to explore the 4 selected gut microbiota from 25 people suffering from rheumatism (RA group) with a time interval of at least 3 years from the onset of the disease and 25 Healthy people by real time PCR. Gut dysbiosis in patients with rheumatoid arthritis (RA) is identified alongside key serological and clinical markers such as C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), immunofluorescence (IF), anti-cyclic citrullinated peptide (Anti-CCP), white blood cell count (WBC), mean corpuscular volume (MCV), aspartate aminotransferase (AST), alanine aminotransferase (ALT), blood urea nitrogen (BUN), Platelet count (PLT), thyroid-stimulating hormone (TSH), creatinine (Cr), and hemoglobin (Hb). Additionally, data from individuals with incomplete or unverified records were excluded from the study to ensure accuracy and reliability. Bacteroides fragilis, Roseburia faecis and Fusobacterium nucleatum genera showed a much lower median in Rheumatoid arthritis patients in comparison with healthy people (P > 0.001, p = 0.002, P < 0.001 respectively). While the difference in the median of E. coli genera was not significant in the two studied groups (p = 0.31). In such a way that the change in the Gut normal flora homeostasis and the reduction of beneficial bacteria such as Bacteroides fragilis, Roseburia faecis, Fusobacterium nucleatum genera, may stimulate the immune system to initiate autoimmunity.